Keys to the 360° narrative through the study of the broadcast of the Goya Awards Gala on RTVE - Caerols Mateo, Raquel (2023)
The push for the use of 360° narratives comes from the popularization of the phenomenon on networks, especially since 2015. In Spain, the Lab de Radio y Televisión Española has been experimenting with this technology, offering recordings of shows and documentaries and pioneering the recording of the first interactive virtual reality episode of a television series. In order to learn about the characteristics, challenges and difficulties of broadcasting 360° events, this paper takes as a case study the broadcasting of the Goya Awards Gala on RTVE. This is a live event where the most outstanding figures of Spanish cinema during the previous year are awarded. The chosen method is based on a previous interview with two people in charge of the RTVE Lab, who are responsible for the 360o production of the gala. Based on the data collected in the interview, a content analysis model was designed and applied to a fragment of the production. From the analysis carried out, it can be deduced that, despite the fact that traditional and 360° broadcasts share formal aspects, there are marked differences between the narratives. Some are designed to be watched (traditional) and others to be experienced (360°). The coexistence between both sign ecosystems is difficult but not impossible, since both types of production share many parameters related to the production of meaning. It is also necessary to standardise 360° technology for a satisfactory first-person experience and acclimatisation on the part of the spectator-user.